Bubble temperature measurements on the binary mixtures of n-heptane or nitrobenzene or chlorobenzene with some chloroethanes and chloroethylenes at (94.6 to 95.8) kPa - Vittal Prasad T.E.; Patanjali V.; Sudhakar T.A.; Radhika B.S.; Arvind V.M.; Prasad D.H.L. (My University, 2025)
Bubble point temperatures at (94.6 to 95.8) kPa, over the entire composition range, were measured for the binary mixtures formed by rc-heptane or nitrobenzene or chlorobenzene with 1,2-dichloroethane, 1,1,1-trichloroethane, 1,1,2,2-tetrachloroethane, trichloroethylene, and tetrachloroethylene by making use of a Swietoslawski type ebulliometer. The liquid-phase composition versus temperature measurements could be well represented by the Wilson model.